ANALISIS PENGARUH KEPUASAN KERJA DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN (Studi pada BPJS Kesehatan Cabang Utama Surakarta) - Ananda Putri, Dea; Rahardjo, Mudji (Diponegoro Journal of Management, 2015)
Job satisfaction and organizational commitment affect employee performance. The purpose of this research is to explain how the variable of job satisfaction and organizational commitment influence to BPJS Kesehatan Cabang Utama Surakarta employee performance. In addition to recognize which variable influences dominantly to the employee performance.The data of this research were collected through a questionnaire distributed to 65 employees of BPJS Kesehatan Cabang Utama Surakarta. Mechanical testing of the data  used  in  this  research  include  the  instrument  test  (validity  and  reliability  test), classical assumption test (normality test, multicoloniarity, and heteroscedasticity test), multiple linear regression analysis, t test, F test, and coefficient of determination test (R2) using SPSS application.The  result  of  this  research  shows  that  job  satisfaction  and  organizational commitment influence positively and significantly to theemployee performance. Variable used   in   this   research   give   positive   response,   meaning   the   job   satisfaction   and organizational commitment improving the performance of BPJS Kesehatan Cabang Utama Surakarta employee. Value of determination coefficient or R2 is 0,364, which means employee performance is affected by job satisfaction and organizational commitment amounted to 36,4%